IOT BERBASIS SISTEM SMART HOME MENGGUNAKAN NODEMCU V3 - Muhammad Aluh; Lita Lidyawati (Jurnal Kajian Teknik Elektro, 2018)
Smart Home is a combination of technology and service in the home environment such as activating electronic equipment that is inside the house with the aim of improving efficiency and comfort. In Smart Home, some home electronic devices or equipment that can be controlled via a smartphone. This research aims to design and make smart home based IoT systems. research methodology using control system development methodology. In its implementation using the NodeMCU V3 module as a link to the internet via wifi, the relay module will be connected to an electronic device and the blynk application via a smartphone that will control all of that. Research results, in access can be activated and turned off via smartphone. The test results, connecting NodeMCU V3 to the internet can be known by looking at the serial monitor in the software used, then the electronic device can be activated and turned off via a smartphone.